Metabolic Pattern of Systemic Sclerosis: Association of Changes in Plasma Concentrations of Amino Acid-Related Compounds With Disease Presentation - Smolenska, Zaneta; Zabielska-Kaczorowska, Magdalena; Wojteczek, Anna; Kutryb-Zajac, Barbara; Zdrojewski, Zbigniew (Frontiers in Molecular Biosciences, 2020)
Objective. Amino acids (AA) and their derivatives play an integral role in the synthesis of structural and regulatory elements in human organisms and therefore pathologies such as systemic sclerosis that may alter blood pattern of these compounds. This study aimed to evaluate changes in plasma concentrations of amino acid-related metabolites in scleroderma in a search for potential biomarkers and mechanisms of the disease. Methods. Plasma samples from 42 patients diagnosed with systemic sclerosis (SSc) according to the 2013 American College of Rheumatology and European League Against Rheumatism ACR/EULAR classification criteria were compared to 27 matched healthy controls. Liquid chromatography/mass spectrometry was applied for the analysis of 36 amino acid-related metabolites. Results. The analysis of plasma metabolite patterns revealed specific changes in SSc: Concentrations of NO synthase (NOS) inhibitor: asymmetric dimethylarginine (ADMA) that increased in patients by 20% vs. healthy subjects. Furthermore, patients had higher glutamine, proline, betaine, 1-methylhistidine and meth-nicotinamide levels, while the concentration of tryptophan was lower. The specific metabolic pattern was identified for several aspects of disease presentation and most interestingly NOS inhibitor L-NAME was elevated in patients with diffuse sclerosis or telangiectasia. Conclusions. These results provide further evidence for the involvement of endothelium-dependent pathways in the mechanisms and presentation of SSc. Endothelial dysfunction biomarkers may be therefore considered as useful in the assessment of SSc.